Emergence and development of weeds according to the sowing depth and light intensity - Marques, Ricardo F. [UNESP]; Souza, Guilherme S. F. [UNESP]; Martins, Cibele C. [UNESP]; de Marchi, Sidnei R.; Martins, Dagoberto [UNESP] (FapUNIFESP (SciELO), 2023)
Understanding weed emergence and development aspects is essential in decision-making for management strategies. The study evaluated the effects of different sowing depths and light intensities on the emergence and development of the weeds Sida rhombifolia and Senna obtusifolia under field conditions. Each species constituted an experiment, and the experimental design used was completely randomized, with four replications. The treatments were arranged in a 6 x 4 factorial scheme, with the first factor corresponding to the six sowing depths (0.5; 1.0; 2.0; 4.0; 8.0, and 12.0 cm) and the second at four light intensities (100%, 70%, 50%, and 30% of sunlight). The seedling emergence was evaluated daily to obtain the emergence and emergence speed index. The height, time to floral induction, and dry matter of plants at flowering were also evaluated. When submitted to different levels of shading, S. rhombifolia seedlings emerge up to 12.0 cm deep. S. obtusifolia seedlings emerge at all sowing depths, even when subjected to different solar radiation intensities. Seedlings of S. rhombifolia and S. obtusifolia emerge less and slower in sowings between 8.0 and 12.0 cm depth and develop better under full sunlight in sowings between 1.0 and 4.0 cm depth. Therefore, greater depths delay the development of both species, which is important information for managing these weeds.
Emergência e desenvolvimento de plantas daninhas em função da profundidade de semeadura e intensidade luminosa
Keywords: Luminosity; Senna obtusifolia; Shading; Sida rhombifolia; Solar radiation